3
$\begingroup$

Let $G$ be a finite group. Let $C_1,C_2,\dots,C_k$ be its conjugacy classes. We denote by $C_{j\ '}=\{g^{-1}|\ g\in C_j\}$ the conjugacy class inverse to $C_j$.

Set $$a_{rst} = \frac{1}{|C_t|}|\{(x,y)\in C_r \times C_s|\ xy\in C_t\}|$$

Prove:

  1. $a_{rst} \in \mathbb{N}_0 =\{0,1,\dots\}$
  2. $a_{rst'} = a_{r' s' t}$

I'm having difficulties proving this problem. Thanks for help !

$\endgroup$
2
$\begingroup$

The claims are relatively straightforward to argue using the group ring $\Bbb Z[G]$. One easily checks that a formal sum in this ring is central iff it commutes with all $g\in G$, iff the coefficients of any two conjugates in $G$ are the same, iff it is a sum of the elements $\sigma_K:=\sum_{x\in K}x$, where $K$ ranges over all the conjugacy classes of $G$. Write $\sigma_i:=\sigma_{K_{\large i}}$. Prove the quotient in (1) is the coefficient of $\sigma_t$ after we expand the product $\sigma_r\sigma_s$ as a sum of $\sigma$s. (The product of central elements is central, and every central element is a sum of $\sigma$s.) Argue $\sigma_r\sigma_s=\sigma_s\sigma_r\Rightarrow a_{rst}=a_{srt}$. Finally, argue an equality equivalent to that in (2), $a_{rst'}=a_{s'r't}$, using $xy=z\Leftrightarrow y^{-1}x^{-1}=z^{-1}$.

$\endgroup$
1
$\begingroup$

After some search I found a more "intuitive" proof as I'm not very familiar with group rings. Feel free to comment & criticize:

Proof of $1.$:
First, if there doesn’t exist $x_0 \in C_r , y_0 \in C_s$ such that $x_0 y_0 \in C_t \Rightarrow a_{rst} = 0 \in \mathbb{N}_0 $.

If there exist such a tuple $x_0 , y_0$ , then we can write $$x_0 y_0 = z_0 \Rightarrow gx_0 y_0 g^{−1} = g z_0 g^{−1} \Rightarrow gx_0 g^{−1} gy_0 g^{−1} = gz_0 g^{−1} \text{ with } g \in G.$$ Now we use the definition of a conjugacy class and see that $gx_0 g^{−1} \in C_r \quad gy_0 g^{−1} \in C_s \quad gz_0 g^{−1} \in C_t $.

Therefore if we find such a tuple $x_0 , y_0$ we can construct $|C_t |$ other tuples. Maybe we find more than one choices of $x_0$ and $y_0$ such that $x_0 y_0 \in C_t$ , lets say there are $n$ such tuples altogether $\Rightarrow$ We can construct $n |C_t |$ such tuples and $|\{(x,y)\in C_r \times C_s|\ xy\in C_t\}|=n |C_t |$ .
Hence $a_{rst} = n \in \mathbb{N}_0$

Proof of $2.$:
Assume $x \in C_r , y \in C_s , z \in C_t , x^{−1} \in C_{r'} , y^{−1} \in C_{s'} , z^{−1} \in C_{t'}$ $$z^{−1} = xy ⇒ x^{−1} z^{−1} = y ⇒ x^{−1} = yz ⇒ x^{−1} y^{−1} = yzy^{−1} ∈ C_t$$ Therefore we find for each tuple $(x,y) \in \{(x,y)\in C_r \times C_s|\ xy\in C_{t'}\}$ an other tuple $(x^{−1} , y^{−1}) \in \{(x,y)\in C_{r'} \times C_{s'}|\ xy\in C_{t}\}$.

As $|C_t|=|C_{t'}|$ we finally have $a_{rst'} = a_{r's't}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.